Absorption of ultrasonic waves in ZnCL2 solutions in methanol - Włodzimierz BOCH (Archives of Acoustics, 2016)
The investigation of the absorption of ultrasonic waves in ZnCl2 solutions in methanol has shown the occurrence of a relaxation process which is considered, in this paper, to be the disintegration and the formation of ion pairs. The activation energy has been determined on the basis of the temperature dependence of the relaxation time of this process, while reaction rate constants have been established from the concentration dependence of the relaxation time. In the solutions investigated a concentration of 2.0 mol/l is a characteristic concentration, above which the structure of the solution becomes considerably stabilized.